Integrating ESG and halal values in shaping Gen-Z consumers’ willingness to pay for biodegradable plastic bags in Malaysia - Ulfy, Mohammad Arijie; Haque, A. K. M. Ahasanul; Abdul Razak, Dzuljastri; Che Embi, Nor Azizan (Human Resource Management Academic Research Society, 2025)
In recent years, biodegradable plastic bags made from renewable resources have gained increasing interest from industries and Gen Z consumers as a solution to environmental problems and in alignment with halal ethics and moral values. Due to the cumulative environmental pollution, new generations are willing to shift towards bio-based polymer bags by preference. The purpose of this study is to investigate the effects of ESG components, i.e., environmental concern, social responsibility, governance sustainability and halal certification trust, on willingness to pay for biodegradable plastic bags among the Generation Z cohort in Malaysia. We collected a total of 367 data points from respondents in the Klang Valley area of Malaysia through an online survey and face-to-face conversations. The data was analysed using partial least squares structural equation modelling (SEM-AMOS). The results show that environmental concern, social responsibility, governance sustainability, and halal certification trust have a significant impact on Generation Z consumers' willingness to pay for biodegradable plastic bags. The findings of this research will be particularly beneficial for both manufacturers, marketers and government authorities to establish effective strategies to meet new generations’ expectations. Therefore, the study will improve the researchers' capacity to identify additional variables for examining the integration of ESG factors and halal values, especially regarding consumers' intentions to purchase sustainable plastic bags